A Cross-Sectional Study on Knowledge, Attitude, and Medication Adherence in Metabolic Syndrome Patients at a Tertiary Care Center in South India - Murugesan, Karthick; Kumar, R. Dinesh; K, Kavibharathi; J, Jeevitha; Babu, Arun; Dhandapani, Shankar (Indian Journal of Pharmacy Practice)
Background: Metabolic Syndrome (MetS) is a major risk factor for cardiovascular disease and type 2 diabetes. Assessing patients’ knowledge, attitudes, and medication adherence is essential for effective management. Materials and Methods: A cross-sectional study was conducted over six months at a tertiary care hospital in South India. A total of 303 patients with MetS were evaluated using the SHIELD and MARS-5 questionnaires. Data were analyzed using descriptive statistics. Results: Overall, 65.0% of patients demonstrated poor knowledge, while 57.4% had a moderate attitude toward MetS. Medication adherence was inadequate, with only 24.4% reporting good compliance. Rural patients showed relatively better knowledge and attitudes but lower adherence compared to urban patients. Conclusion: Patients with MetS exhibited inadequate knowledge, moderate attitudes, and poor medication adherence. Targeted educational strategies and adherence-focused interventions are urgently needed to improve disease management and outcomes.
Keywords: Metabolic Syndrome; Knowledge; Attitude; Medication Adherence; South India